All-sputtered oxide thin-film transistors fabricated at 150 °C using simultaneous ultraviolet and thermal treatment. Issue 2 (14th December 2017) - Tak, Young Jun; Kim, Si Joon; Kwon, Sera; Kim, Hee jun; Chung, Kwun-Bum; Kim, Hyun Jae
Abstract : An all-sputtered oxide TFT process combined with simultaneous ultraviolet and thermal (SUT) treatment for consecutive fabrication processes at low temperatures. Abstract : In this study, we report all-sputtered In–Ga–Zn–O (IGZO) thin-film transistors (TFTs) through the fabrication of a sputtered gate insulator. Furthermore, using simultaneous UV and thermal (SUT) treatment, we fabricate sputter-processed gate insulators at a low temperature of 150 °C with a higher amount of coordinated oxygen species and a higher surface energy than thermal-only (300 °C) treated gate insulators. Additionally, by activating the IGZO channel layer using SUT treatments, we fabricate all-sputter processed IGZO TFTs at 150 °C and they exhibit improved device performances compared to thermal-only treated ones; the field-effect mobility is increased from 7.32 ± 3.8 to 29.59 ± 2.5 cm 2 V −1 s −1, the on/off ratio is increased from (1.1 ± 1.8) × 10 5 to (2.9 ± 1.7) × 10 8, and the subthreshold swing is decreased from 1.0 ± 0.07 to 0.4 ± 0.05 V dec −1 .